Peran Pemerintah Kabupaten Jember dalam Rangka Pembinaan, Pengawasan Kegiatan Tambang di Kabupaten Jember - Yuli Winiari Wahyuningtyas (Fakultas Hukum Universitas Islam Jember, 2018)
In addition to the great potential in agriculture, Jember Regency also has another potential, one of which is in the mining sector. According to data sources from the Jember Information Center, the potential for mining in both sand, iron, manga and mines in Jember Regency is spread in several districts, namely: Puger, Wuluhan, Ambulu, Silo, Pakusari, Ledokombo and Sukowono Subdistricts. The existence of various regional potentials initiated the Jember Regency Government to make Regional Regulations namely Regional Regulation No. 1 of 2015 concerning the Jember Regency Spatial Planning as an effort to regulate the Jember area both in the infrastructure and potential sectors of the local area. Related to licensing, Regional Regulation No. 1 of 2015 concerning the Regional Spatial Planning of the Jember Regency RTRW states under the direction of licensing in the form of licenses related to space utilization permits which must be held according to the provisions of legislation before the implementation of spatial utilization.